The Relationship Of Water Source Location And Physical Quality Of Water With The Event Of Diarrhea In Toddlers (in Purwodadi Village, Purwodadi District, Pasuruan Regency) - Rusdi, Warda El Maida; Pramistyowati , Magda Budi; Farindra, Irmawan; Irawan, Danny (Jurnal Ilmu Kesehatan dan Kesehatan, 2022)
Background: Diarrheal disease is a health problem until now and is the leading cause of death in toddlers. It is also supported by environmental sanitation and personal hygiene of the community which is still poor. The use of bad water sources will also affect the quality of the water, so it can increase the risk of diarrhea in the community. Method: This type of research is analytical observational with cross sectional design. The samples used were 75 out of a population of 523 mothers who had toddlers and lived in Purwodadi Village, Purwodadi Subdistrict, Pasuruan Regency, with purposive sampling techniques. Using questionnaire method, as well as statistical test using chi-square with the help of computer software. Result: The results of this study showed that there was a significant association between the location of the sheltered water source as many as 38 respondents (50.7%) and unprotected as many as 37 respondents (49.3%) with a value of p = 0.003, as well as the physical quality of water that qualified as many as 37 respondents (49.3%) and did not qualify as many as 38 respondents (50.7%) with a value of p = 0.000, against the incidence of diarrhea in toddlers, where the value of p ≤ 0.05. Conclusion: Location of water source and physical quality of water is related to the incidence of diarrhea in toddlers